Good role models? Tooth brushing capabilities of parents: a video observation study - Renate Deinzer; Sadhvi Shankar-Subramanian; Alexander Ritsert; Stefanie Ebel; Bernd Wöstmann; Jutta Margraf-Stiksrud; Zdenka Eidenhardt (BMC, 2021)
Abstract Background Research in adolescents reveals that they are not capable to remove dental plaque effectively. Inconsistent application of brushing techniques and neglect of certain areas while brushing are very common. As parents play a major role in the oral health education, the present study aimed to examine and describe the tooth brushing performance of the parents of adolescents. Methods Parents of adolescents (N = 66) were asked to perform oral hygiene to the best of their capabilities in front of a video camera and dental plaque was recorded before and afterwards. Papillary bleeding was also assessed. Results The tooth contact time (i.e. net brushing duration) averaged 155 s ± 58 s. Gingival margins showed persistent plaque at 68% ± 14% of the sections assessed. Papillary bleeding was found at 52% ± 18% of the papillae. Parents brushed inner surfaces lesser than the outer surfaces (41 s ± 24 s vs. 73 s ± 33 s) and 29% of the parents completely missed the inner surfaces of at least one sextant. On the outer surfaces parents predominantly applied circular movements (66% ± 25% of brushing time). Vertical brushing prevailed on the inner surfaces (52% ± 30%). However, horizontal scrubbing was also very common (46% ± 31%). Conclusions Parents' tooth brushing performance was neither effective in terms of plaque removal nor did they fully comply with tooth brushing recommendations such as considering all inner surfaces when brushing or application of other than horizontal movements to lateral surfaces. Regarding oral hygiene, parents should not only be a good role model in terms of timing, frequency and duration of tooth brushing but should also be able to demonstrate how to brush teeth completely and effectively. The current research indicates that they might lack the latter skill.